Pengaruh Mekanisme Corporate Governance terhadap Kinerja Keuangan dengan Ukuran Perusahaan Sebagai Variabel Kontrol - Nuriya Anaima; Sri Trisnaningsih (Universitas Indo Global Mandiri)
One of the good applications of the company's management mechanism system in supporting financial performance is called Good Corporate Governance (GCG). The purpose of this research is to know and prove empirically the effect of good corporate governance on financial performance in the consumer goods industry sector listed on the IDX for the period 2017 - 2019. Good Corporate Governance (GCG) is measured by several indicators, namely the intensity of audit committee meetings and the proportion of the board independent commissioners using the control variable, namely company size. The financial performance in this study uses the Return On Asset (ROA) indicator. This research is quantitative with multiple regression analysis assisted by IBM SPSS statistics 22 software. From the purposive sampling technique that has been used, a sample of 34 companies from 45 companies in the consumer goods industry sector was obtained. From the analysis that has been done, the results show that there is a simultaneous significant influence on the intensity of audit committee meetings and the proportion of independent commissioners with company size as the control variable. Based on individual testing, there is a significant effect on the proportion of independent commissioners and company size on financial performance, but the intensity of the audit committee meeting has no significant effect on financial performance.Keywords: effectiveness of audit committee, proportion of independent commissioners, board of directors size, return on asset (ROA).